ABDULLAH SAEED’S CONTEXTUALIST PERSPECTIVE ON THE FIQH OF RELIGIOUS FREEDOM - Fadhilah, Eva (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2019)
One areas of conflict between international human rights law and traditional Islamic law is the question of religious freedom. The classical Islamic law provision on the capital punishment for riddah (apostasy) is particularly considered as contradictory with international human rights norms. Some contemporary Muslim scholars, however, have proposed a fresh thinking in dealing with this tension. This paper seeks to examine the thinking of Abdullah Saeed as one of leading Muslim scholars in the contemporary debate on this issue. It argues that Abdullah Saeed is one of the modern thinkers positioning Human Rights as global ethics that must be admitted in the modern era. With his contextual methodology, he put forward an argument that Islam should be open to the idea of religious freedom as stipulated in the Universal Declaration of Human Rights and that the right to have religion and belief has become a vertical matter between humans and God.